Pengaruh Harga, Kualitas Produk, Dan Iklan Terhadap Pengambilan Keputusan Pembelian Pada Marketplace Shopee (Studi pada mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Aldiansyah Damar Affandi; Agus Widarko; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract A data collection method using a questionnaire. The analytical methods used are instrumental testing, multiple linear regression analysis, classical assumption testing, decision testing, and f-test and t-test using SPSS16.0 computer software for data processing. This is shown by the results of this study price has an effect on purchasing decisions, product quality has an effect on purchasing decisions and advertising has an effect on purchasing decisions. Price, product quality and advertising simultaneously affect purchasing decisions. Keywords: Price, Product Quality, Advertising And Purchase Decision.